Analisis Tingkat Efisiensi Organisasi Pengelola Zakat (Opz) Di Indonesia Dengan Menggunakan Data Envelopment Analysis (Dea) Periode 2013-2015 - Syahadah, Wafiatusy, Eny Setyowati,SE.M.Si (2017)
This research entitled "Analysis Of Efficiency Zakat Management Organization (OPZ) in Indonesia By Using Data Envelopment Analysis (DEA) 2013-2015 period. This reseach is aimed to analyze the efficiency of Zakat Management Organization (OPZ) in Indonesia firmed by the goverment among Zakat Management Organization (OPZ) used in this reseach, they are National Zakat Agency (BAZNAS), Islamic Baitulmaal Of Bank Negara Indonesia (BAMUIS BNI), and Baitul Maal Foundation Of Bank Rakyat Indonesia (YBM BRI). This reseach uses secondary data from financial report whice is published by each Zakat Management Organization (OPZ). This reseach uses input-output variabel with Data Envelopment Analysis (DEA). The result of the reseach show there was only one Zakat Management Organization (OPZ) is having inefficiency from 2013-2015 period. Based on calculation using Data Envelopment Analysis (DEA) in 2013 BAZNAS having efficiency while BAMUIS BNI, and YBM BRI had showed efficiency in 2014-2015, BAZNAS, BAMUIS BNI, and YBM BRI have had 100 efficiencies continnously until that period. Keywords: Zakat Management Organization, Efficiency, Data Envelopment Analysis (DEA)